Granular cell tumour of the neurohypophysis: an unusual cause of hypopituitarism - Carlos Tavares Bello; Patricia Cipriano; Vanessa Henriques; João Sequeira Duarte; Conceição Canas Marques (Endocrinology, Diabetes & Metabolism Case Reports, 2018)
Granular cell tumours (GCT) are rare, slow-growing, benign neoplasms that are usually located in the head and neck. They are more frequent in the female gender and typically have an asymptomatic clinical course, being diagnosed only at autopsy. Symptomatic GCT of the neurohypophysis are exceedingly rare, being less than 70 cases described so far. The authors report on a case of a 28-year-old male that presented to the Endocrinology clinic with clinical and biochemical evidence of hypogonadism. He also reported minor headaches without any major visual symptoms. Further laboratory tests confirmed hypopituitarism (hypogonadotrophic hypogonadism, central hypothyroidism and hypocortisolism) and central nervous system imaging revealed a pituitary macroadenoma. The patient underwent transcranial pituitary adenoma resection and the pathology report described a GCT of the neurohypophysis with low mitotic index. The reported case is noteworthy for the rarity of the clinicopathological entity.